Commissioning management : CIBSE CCM: 2022 (Chartered Institution of Building Services Engineers (CIBSE), 2022)
Buildings and engineering systems need to be safely delivered within specific cost, time and build-quality parameters. They also need to be operationally ready at handover; perform to meet the specified needs of the people that use, manage, operate and maintain them; and function safely and efficiently in the long-term. In a world of accelerating technological advancement, increasing building complexity, tightening regulatory constraints, growing consumer demand for quality, surging environmental consciousness, and an urgent need to de-carbonise buildings, commissioning is one of the most important ways to achieve these outcomes. The purpose of commissioning management is to ensure that commissioning is correctly executed - and that people, businesses, society, and the environment all benefit as a result. The original version of this Code was produced in 2003. This updated document is intended to better represent the modern perception of what commissioning is and to reflect current commissioning management best practices.